Acute Kidney Injury In Ugandan Children With Severe Malaria Is Associated With Long-Term Behavioral Problems - Hickson, Meredith R.; Conroy, Andrea L.; Bangirana, Paul; Opoka, Robert O.; Idro, Richard; Ssenkusu, John M.; John, Chandy C. (PloS one, 2019)
Acute kidney injury (AKI) is a risk factor for neurocognitive impairment in severe malaria (SM), but the impact of AKI on long-term behavioral outcomes following SM is unknown.We conducted a prospective study on behavioral outcomes of Ugandan children 1.5 to 12 years of age with two forms of severe malaria, cerebral malaria (CM, n = 226) or severe malarial anemia (SMA, n = 214), and healthy community children (CC, n = 173). AKI was defined as a 50% increase in creatinine from estimated baseline. Behavior and executive function were assessed at baseline and 6, 12, and 24 months later using the Child Behavior Checklist and Behavior Rating Inventory of Executive Function, respectively. Age-adjusted z-scores were computed for each domain based on CC scores. The association between AKI and behavioral outcomes was evaluated across all time points using linear mixed effect models, adjusting for sociodemographic variables and disease severity.AKI was present in 33.2% of children with CM or SMA at baseline. Children ≥6 years of age with CM or SMA who had AKI on admission had worse scores in socio-emotional function in externalizing behaviors (Beta (95% CI), 0.52 (0.20, 0.85), p = 0.001), global executive function (0.48 (0.15, 0.82), p = 0.005) and behavioral regulation (0.66 (0.32, 1.01), p = 0.0002) than children without AKI. There were no behavioral differences associated with AKI in children <6 years of age.AKI is associated with long-term behavioral problems in children ≥6 years of age with CM or SMA, irrespective of age at study enrollment.